System symboli-komunikatów wspomagający komunikację na przykładzie firmy projektowej - Korczyńska, Maria; Tracz, Ewa (System of symbols-messages supporting communication: the case of a design company, 2005)
Effective communications determines efficiency of a modem enterprise. Actually several communication barriers and techniques to overcome them exist in practice. In the article one of such solutions is presented (developed for a Design Company); it was inspired by visual management applied within the Kanban system. The solution is based on a simple system of symbols-messages, which can be exploited by all Company's employees
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 280-286